1991
DOI: 10.1016/0370-2693(91)90057-w
|View full text |Cite
|
Sign up to set email alerts
|

Off-shell WZW models in extended superspace

Abstract: Off-shell WZW models in extended superspaceSchoutens, C.J.M.; Rocek, M.; Sevrin, A. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University of Amsterdam, Secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
195
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(200 citation statements)
references
References 19 publications
5
195
0
Order By: Relevance
“…A superfield formulation has also been constructed for some (2,2)-supersymmetric sigma models with on-shell supersymmetry and target spaces complex manifolds [5]. We have shown that there are off-shell (2,0)-supersymmetric sigma models with target spaces almost complex manifolds.…”
Section: Discussionmentioning
confidence: 93%
“…A superfield formulation has also been constructed for some (2,2)-supersymmetric sigma models with on-shell supersymmetry and target spaces complex manifolds [5]. We have shown that there are off-shell (2,0)-supersymmetric sigma models with target spaces almost complex manifolds.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, in [5] it was shown that only on SU(2) × U(1) a choice for j andj can be made such that [J,J] = 0. There a description in terms of a chiral and a twisted chiral field is possible.…”
Section: Examplesmentioning
confidence: 99%
“…Having an extended superspace description of these models yields various simplifications and applications. The geometry becomes transparant and duality transformations can be performed which keep the extended supersymmetry manifest [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In [10], N = (4, 4) superextensions of other groupmanifold WZNW models were constructed, and the exhaustive list of group manifolds for which such extensions exist was given (they are those admitting a quaternionic structure). Superfield formulations of N = (4, 4) models were given in N = (2, 2) superspace [8], in ordinary N = (4, 4) superspace [11,12], in the projective superspace [13,14] and in the N = (4, 4), SU(2) × SU(2) bi-harmonic superspace [15] - [18]. The N = (4, 4) superfield formulations are most appropriate, as they make manifest and off-shell the full amount of the underlying supersymmetry.…”
Section: Introductionmentioning
confidence: 99%